Temperature seasonality during fry out‐migration influences the survival of hatchery‐reared chum salmon Oncorhynchus keta. Issue 4 (16th September 2015) - Morita, K.; Nakashima, A.
<x xml:space="preserve">Abstract</x> Among years, fry‐to‐adult survival of hatchery‐reared chum salmon Oncorhynchus keta was positively correlated with the length (in days) of the fry out‐migration period with temperatures suitable for migration. Furthermore, survival decreased with increasing difference in mean temperature between May and June. Thus, prolonged out‐migration periods increased the probability of survival from fry to adult, lending support to the hypothesis that long migration periods decrease the risk of mortality (bet‐hedging), and increase the probability of migration when environmental conditions in fresh water and the ocean are suitable (match–mismatch).